Analisis Pasar Wisatawan Nusantara di Candi Borobudur - Rakhman, Cecep Ucu (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
This is a marketing research in the tourism sector that discusses the market segmentation of domestic tourists (wisnus) in Borobudur Temple. This study analyzed the profile of the wisnus using quantitative research. Methods of data collection were conducted with questionnaires, field observations, and documentation studies. The results showed that tourists who visited Borobudur Temple mostly came from outside the province (62%) and within the province (38%). When viewed from the provincial origin, then the five largest provinces are domestic tourists from Central Java Province of 38%, while respondents who come from the West Java Province of 13 %. Then the respondents from D.l. Yogyakarta with 10%, then East Java Province 9 and DKI Jakarta 9%. Respondents who visited Borobudur Temple were 15-24 years old (36%), male (58%), married (52%), graduated from diploma (46%), still in student status (27%), Revenue per month <Rp. 2,000, 000.00 (52%). The majority of respondents have preference type DTW historic sites (52%), preferences for recreational activities (81%), art and culture (53%), friend / family sources (53%), family (52%), had no constraints (43%), day preference on national holidays (39%), in the morning (57%), duration of l -3 hours (65%), visitfrequency 1 times (80%), average / moderate price perception (75%), rate of Borobudur temple at good enough level (58%), and have hope for improvement of DTW (45%) location arrangement. Spending at DTW> Rp. 50.000,00 (28%), total expenses during trip <Rp. 200.000,00 (32%), the largest share of expenditure is located on transportation (34%), using land transportation (86%) and air (13%), visiting reason because Borobudur Temple has artistic and cultural value (38%), preference of stay in other hotels / inns (36%), visit planning <1 week earlier (65%), recommend Borobudur Temple (96%), and have a return visit (97%). In comparison of markets within and outside the province, the source of information from friends /family (62%) is preferred by the market within the province. Outside provincial markets (85%) have motivational preferences of visiting for recreation and leisure. The average income of domestic tourists in the province is Rp. 3.138.298 Meanwhile, the average income of tourists outside the province is Rp.3.750.000. Expenditure at Borobudur Temple for respondents in the province is Rp.194.681, - meanwhile for out ofprovince is Rp.202.885. 000, -. Travelers from within the province have an average total of travel expenses ofRp.606.383 and outside the province ofRp.1.264.744. Nusantara tourists in the province have purchasing power of 19% of income per month while from outside the province have purchasing power of 34% of tourist income per month. For the largest expenditure during the trip is on transportation, tourists outside the province has a magnitude of 36% and tourists in the province of 32%. For the category recommend, tourists outside the province have 95% and tourists in the province of 98%. The appraisal of tourism facilities is at a sufficiently good level with a value of 3.50, all price aspects considered to have a range between 3.25 - 3.46 infrastructure components and promotion is quite good with an average score of 3.55.